Capillary Water Absorption Characteristics of Steel Fiber-Reinforced Concrete - Fang Nan; Qing Shen; Shuang Zou; Haijing Yang; Zhenping Sun; Jingbin Yang (Buildings)
The water absorption behavior of concrete is a critical indicator of its durability, and a comprehensive understanding of water transport characteristics can significantly enhance concrete performance. This study investigates the capillary water absorption properties of steel fiber-reinforced concrete across various strength grades by combining mercury intrusion porosimetry (MIP) and 1H low-field nuclear magnetic resonance (1H low-field NMR) techniques. Key findings reveal that the capillary water absorption of steel fiber-reinforced concretes occurs in the following two distinct stages: an initial rapid absorption phase (0 min to 6 h) and a subsequent slow absorption phase (1 day to 12 days). Modifications to the concrete matrix composition substantially reduce capillary water absorption rates, with ultra-high-performance concrete (UHPC) exhibiting exceptionally low absorption levels (the cumulative capillary water absorption of UHPC accounts for only 4.5–5.7% of that of C30 concrete). Additionally, for higher-strength concrete and extended absorption durations, the capillary water absorption rate deviates from the linear relationship with the square root of time. This deviation is attributed to the interaction of gel pore water with unhydrated cement particles, generating more hydration products, which refine the pore structure, reduce capillary pore connectivity, and increase pore tortuosity. Furthermore, steel fibers influence water transport through the following two primary mechanisms: interfacial interactions between the fibers and the matrix and a physical blocking effect that impedes water movement.